2003
DOI: 10.2214/ajr.180.6.1801613
|View full text |Cite
|
Sign up to set email alerts
|

Videofluoroscopic Studies of Swallowing Dysfunction and the Relative Risk of Pneumonia

Abstract: Our findings indicate that the likelihood of developing pneumonia is directly related to the degree of swallowing dysfunction seen on videofluoroscopic studies. Patients with no laryngeal penetration-regardless of whether they had normal or abnormal swallowing-have the lowest risk of developing pneumonia. Patients with laryngeal penetration, tracheobronchial aspiration, or silent tracheobronchial aspiration are, in increasing order of magnitude, significantly more likely to develop pneumonia than patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
144
0
14

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(169 citation statements)
references
References 15 publications
9
144
0
14
Order By: Relevance
“…8 The combination of recurrent aspiration in the setting of immune deficiency can be particularly injurious to the lung. 9,10 Impaired coordination may also extend to the respiratory system, adversely affecting respiratory muscle strength and impairing cough. Maximal expiratory efforts are needed to generate effective coughs and to clear airway secretions.…”
Section: Introductionmentioning
confidence: 99%
“…8 The combination of recurrent aspiration in the setting of immune deficiency can be particularly injurious to the lung. 9,10 Impaired coordination may also extend to the respiratory system, adversely affecting respiratory muscle strength and impairing cough. Maximal expiratory efforts are needed to generate effective coughs and to clear airway secretions.…”
Section: Introductionmentioning
confidence: 99%
“…Laryngeal penetrations were reported to be significantly more frequent after the age of 50 during normal aging 26. Despite the fact that laryngeal penetration is also observed in healthy controls, people without laryngeal penetration were reported to have the lowest risk of developing pneumonia compared with patients with laryngeal penetration or aspiration 27. A previous report using fiberoptic endoscopy also found that patients with SBMA have pharyngeal residues 28.…”
Section: Discussionmentioning
confidence: 97%
“…Estudos mostram que pacientes com comprometimento neurológico apresentam lentidão e falta de controle das estruturas, relacionadas às fases preparatória e oral da deglutição (19)(20)(21)(22)(23)(24) , aumentando a quantidade de resíduos alimentares em valéculas e/ou recessos piriformes, o que acarreta maior risco para a penetração laríngea e/ou aspiração traqueal pós-deglutição (4) . A presença de penetração laríngea apresentou maior incidência na administração da consistência líquida, em 40,5% (15/43), seguida da pastosa fina em 37,8% (14/43), pastosa grossa em 27% (10/43) e sólida, em 21,6% (8/43).…”
Section: Discussionunclassified